2018
DOI: 10.1590/s1677-5538.ibju.2017.0283
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury following radical cystectomy and urinary diversion: predictors and associated morbidity

Abstract: Introduction:Acute kidney injury (AKI) after major surgeries is associated with significant morbidity and mortality. We aim to report incidence, predictors and associated comorbidities of AKI after radical cystectomy in a large cohort of patients.Materials and Methods:We conducted a retrospective analysis of 1000 patients who underwent open radical cystectomy in a tertiary referral center. Perioperative serum creatinine measurements were used to define AKI according to the RIFLE criteria (as Risk, Injury and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Osman Y et al reported that acute kidney injury developed in 46 (4.7%), patients after radical cystectomy. While 11 (1.1%), patients developed progressive deterioration of renal function [14].…”
Section: Discussionmentioning
confidence: 94%
“…Osman Y et al reported that acute kidney injury developed in 46 (4.7%), patients after radical cystectomy. While 11 (1.1%), patients developed progressive deterioration of renal function [14].…”
Section: Discussionmentioning
confidence: 94%
“…24,25 Postoperative factors consist of infection and postrenal obstruction. 12,13,22,23,26 Derived from this insight, the following intraoperative strategies have been proposed: a restrictive-deferred hydration strategy avoiding episodes of intraoperative hypotension while maintaining sufficient perfusion pressure by using continuous noradrenaline infusion instead of excessive fluid administration. 15,25,27 The time between induction of anesthesia and surgical incision warrants special attention as a relevant share of hypotensive events occur during this period.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative factors are prolonged time of surgery (>400 min), significant blood loss, episodes of hypotension, and surgical complications 24,25 . Postoperative factors consist of infection and postrenal obstruction 12,13,22,23,26 . Derived from this insight, the following intraoperative strategies have been proposed: a restrictive‐deferred hydration strategy avoiding episodes of intraoperative hypotension while maintaining sufficient perfusion pressure by using continuous noradrenaline infusion instead of excessive fluid administration 15,25,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is recognized as a severe complication of advanced cirrhosis, and is similarly known to be a common complication amongst patients undergoing major abdominal surgery, including radical cystectomy [93][94][95]. Hepatorenal syndrome (HRS) in particular, which falls under the larger umbrella of etiologies contributing to AKI, results from decreased renal blood flow in patients with advanced cirrhosis.…”
Section: Hepatorenal Syndromementioning
confidence: 99%